2011
DOI: 10.4103/0019-5154.77547
|View full text |Cite
|
Sign up to set email alerts
|

Steroid - induced rosacea: A clinical study of 200 patients

Abstract: Background:Topical corticosteroids were first introduced for use in 1951. Since then uncontrolled use (abuse) has caused many different reactions resembling rosacea – steroid dermatitis or iatrosacea. Multiple pathways including rebound vasodilatation and proinflammatory cytokine release have been proposed as the mechanism for such reactions.Aim:The aim was to study the adverse effects of topical steroid abuse and the response to various treatment modalities.Materials and Methods:Two hundred patients with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 8 publications
3
74
1
3
Order By: Relevance
“…In our study, acne aggravation and acneiform eruption due to TCs was seen in 35% patients. 8,12 This is almost similar to the result of study by Bhat YJ et al reporting 35% patients with acneiform eruption. 10 Brar KB et al observed acneiform eruption in 56% cases as the most common side effect.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, acne aggravation and acneiform eruption due to TCs was seen in 35% patients. 8,12 This is almost similar to the result of study by Bhat YJ et al reporting 35% patients with acneiform eruption. 10 Brar KB et al observed acneiform eruption in 56% cases as the most common side effect.…”
Section: Discussionsupporting
confidence: 82%
“…[15] Persistent use of TCS can also lead to complications such as epidermal atrophy, degeneration of dermal structure with decrease collagen synthesis, rosacea, and susceptibility to superficial bacterial, viral and fungal infections. [14] Almost all these adverse effects were observed in our patients.…”
Section: Discussionmentioning
confidence: 85%
“…[15] Various other terms have been used by authors describing this entity such as topical steroid dependent face (TSDF), red face syndrome, steroid dermatitis resembling rosacea (SDRR) and steroid rosacea. [14] TSDF is a new entity characterized by erythema or burning sensation or pruritus on attempted cessation of TCS application. [15] Persistent use of TCS can also lead to complications such as epidermal atrophy, degeneration of dermal structure with decrease collagen synthesis, rosacea, and susceptibility to superficial bacterial, viral and fungal infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings with some variations were observed in other studies. [14][15][16] It has been suggested that multiple pathways including rebound vasodilatation and pro-inflammatory cytokine release by chronic steroid use induce erythema and rosacea-like eruption. 17 Most of the patients in our study (68%) used potent to very potent TCs, which is in concordance with aforementioned studies from other studies.…”
Section: Discussionmentioning
confidence: 99%